2006
DOI: 10.4049/jimmunol.176.7.4125
|View full text |Cite
|
Sign up to set email alerts
|

CD4+ Regulatory T Cells Are Spared from Deletion by Antilymphocyte Serum, a Polyclonal Anti-T Cell Antibody

Abstract: Broad T cell depletion has been used as an integral part of treatment in transplantation and autoimmune diseases. Following depletion, residual T cells undergo homeostatic proliferation and convert to memory-like T cells. In this study, we investigated the effect of T cell depletion by antilymphocyte serum (ALS), a polyclonal anti-T cell Ab, on CD4+ regulatory T cells. After ALS treatment, CD4+CD25+ T cells underwent proliferation and expressed a memory T cell marker, CD44. One week after ALS treatment, both C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
76
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(81 citation statements)
references
References 39 publications
5
76
0
Order By: Relevance
“…Interestingly, polyclonal anti-lymphocyte serum has also been shown to spare the CD4 ϩ CD25 ϩ Tregs from deletion although it deletes most of the other lymphocytes. At least 2 wk after anti-lymphocyte serum treatment it appeared that the residual CD4 ϩ CD25 ϩ Tregs showed a much stronger in vitro suppressive activity (48). Although the mechanisms of the above polyclonal anti-lymphocyte sera appear complex, our data collectively suggest that anti-TCR Ab-mediated activation of the CD8␣␣ Tregs in vivo provides an important pathway for generating an effective regulatory response with potential clinical implications for the therapy of autoimmune diseases and transplant rejections.…”
Section: Figurementioning
confidence: 75%
“…Interestingly, polyclonal anti-lymphocyte serum has also been shown to spare the CD4 ϩ CD25 ϩ Tregs from deletion although it deletes most of the other lymphocytes. At least 2 wk after anti-lymphocyte serum treatment it appeared that the residual CD4 ϩ CD25 ϩ Tregs showed a much stronger in vitro suppressive activity (48). Although the mechanisms of the above polyclonal anti-lymphocyte sera appear complex, our data collectively suggest that anti-TCR Ab-mediated activation of the CD8␣␣ Tregs in vivo provides an important pathway for generating an effective regulatory response with potential clinical implications for the therapy of autoimmune diseases and transplant rejections.…”
Section: Figurementioning
confidence: 75%
“…Recently, it has been shown that more than just acting as a T cell depletion agent, rATG is able to induce a significant increase of Treg in vitro (25), although it has been suggested that Tregs are quite sensitive to elimination by depleting Abs (45). However, it has also pointed out that the relative resistance of Tregs to apoptosis can promote tolerance through preferential depletion of Teffector cells (46,47). In contrast, optimal concentrations of rATG for in vitro generation of Tregs appear to occur at significantly lower levels than those achieved in serum after treatment with standard rATG doses in vivo (42,48).…”
Section: Discussionmentioning
confidence: 99%
“…2b). The relative resistance of this T cell subset to various conditioning regimes (29,47), as well as depletion by HIV infection (48,49), has been reported previously.…”
Section: Characteristics Of T Cell Depletion Induced By Treatment Witmentioning
confidence: 99%